Pengaruh Jenis Media Tanam dan Jenis Sumbu terhadap Pertumbuhan dan Hasil Bayam Merah secara Hidroponik - Arki Vanesaputri; Setiyono Setiyono; Ayu Puspita Arum (Universitas Sebelas Maret, 2022)
Hydroponics is a narrow land planting system that uses rockwool and flannel as planting media which has disadvantage of being expensive and difficult to obtain, so it requires local materials as a substitute of planting media which must be tested for the effectiveness of using the type of media and its axes. Therefore, the purpose of this study was to determine the effect of the type of planting medium and the type of axis. The research was conducted factorially using Split Plot Design with the archetype of goup plot design (RAK) consisting of 2 factors with 3 repeats. The first factor as the main tile was type of media consisting of three levels; rockwool, cocopeat, and charcoal husk, while the second factor as sub plots were types of axes consisting of three levels; flannel, coconut coir fiber, and banana smelter fiber. The results showed that the interaction on types of media and axes had an unreally different influence on all observational variables except root volume variable; The types of media had an unreally different response to all observational variables; The types of axes had a different response which was not noticeable in plant height, root length, and header / root ratio, but It had a noticeable different response to variables in the number of leaves, root volume, fresh weight of the plant, and dry weight of the plant, in which flannel showed the best results. So, the type of media and axis affected the gowth of red spinach in hydroponic system.